Randomized Phase III study of gemcitabine plus S-1 versus gemcitabine plus cisplatin in advanced biliary tract cancer: Japan Clinical Oncology Group Study (JCOG1113, FUGA-BT) - Mizusawa, Junki (Jpn J Clin Oncol, 2016)
A Phase II selection design trial was conducted to identify the most promising regimen for comparison with standard therapy in chemo-naive patients with unresectable or recurrent biliary tract cancer (JCOG0805). Gemcitabine plus S-1 therapy showed better efficacy than S-1 monotherapy with acceptable safety in JCOG0805 study. Based on this result, a randomized Phase III trial was started in May 2013 to confirm the non-inferiority of gemcitabine plus S-1 therapy relative to gemcitabine plus cisplatin therapy, which is the current standard treatment for chemo-naive patients with unresectable or recurrent biliary tract cancer. A total of 350 patients will be accrued from 32 Japanese institutions within 4 years. The primary endpoint is overall survival, while the secondary endpoints are progression-free survival, adverse events, serious adverse events, clinically significant adverse events, response rate and %planned dose. This trial has been registered with the UMIN Clinical Trials Registry (http://www.umin.ac.jp/ctr/index.htm) and the registration number is UMIN000010667.